Ethnobotany of Mexican and northern Central American cycads (Zamiaceae) - Mark Bonta (Journal of Ethnobiology and Ethnomedicine, 2019)
Abstract Background This study documents cycad-human relationships in Mexico, Belize, Guatemala, El Salvador, and Honduras over the last 6000 years. The impetus was acute need for a better understanding of previously undocumented uses of cycads in this region, and the need to improve cycad conservation strategies using ethnobotanical data. We hypothesized that cycads are significant dietary items with no long-term neurological effects, are important to religious practice, and contribute to cultural identity and sense of place, but that traditional knowledge and uses are rapidly eroding. Guiding questions focused on nomenclature, food and toxicity, relationships to palms and maize, land management issues, roles in religious ceremony, and medicinal uses, among others, and contributions of these to preservation of cycads. Methods From 2000 to 2017, the authors conducted 411 semi-structured ethnographic interviews, engaged in participant-observation in Mexican and Honduran communities, and carried out archival research and literature surveys. Results We documented 235 terms and associated uses that 28 ethnic groups have for 57 species in 19 languages across 21 Mexican states and 4 Central American nations. Carbohydrate-rich cycads have been both famine foods and staples for at least six millennia across the region and are still consumed in Mexico and Honduras. Certain parts are eaten without removing toxins, while seed and stem starches are detoxified via several complex processes. Leaves are incorporated into syncretic Roman Catholic-Mesoamerican religious ceremonies such as pilgrimages, Easter Week, and Day of the Dead. Cycads are often perceived as ancestors and protectors of maize, revealing a close relationship between both groups. Certain beliefs and practices give cycads prominent roles in conceptions of sense of place and cultural heritage. Conclusions Cycads are still used as foods in many places. Though they do not appear to cause long-term neurological damage, their health effects are not fully understood. They are often important to religion and contribute to cultural identity and sense of place. However, because most traditional knowledge and uses are rapidly eroding, new community-based biocultural conservation efforts are needed. These should incorporate tradition where possible and seek inspiration from existing successful cases in Honduras and Mexico.